Early-Onset Preeclampsia Is Associated With Gut Microbial Alterations in Antepartum and Postpartum Women - Lv, Li-Juan; Li, Sheng-Hui; Li, Shao-Chuan; Zhong, Zhi-Cheng; Duan, Hong-Li; Tian, Cheng; Li, Hui; He, Wei; Chen, Min-Chai; He, Tian-Wen; Wang, Yu-Nan; Zhou, Xin; et al. (Frontiers in Cellular and Infection Microbiology, 2019)
Background: Imbalances in gut microbiota composition are linked to hypertension, host metabolic abnormalities, systemic inflammation, and other conditions. In the present study, we examined the changes of gut microbiota in women with early-onset preeclampsia (PE) and in normotensive, uncomplicated pregnant women during late pregnancy and at 1 week and 6 weeks postpartum. Methods: Gut microbiota profiles of women with PE and healthy pregnant women in the third trimester and at 1 week and 6 weeks postpartum were assessed by 16S rRNA gene amplicon sequencing. Plasma levels of interleukin-6 (IL-6), intestinal fatty acid-binding protein (I-FABP), zonulin and lipopolysaccharide (LPS) were measured in the third trimesters. Results: At the genus level, 8 bacterial genera were significantly enriched in the antepartum samples of PE patients compared to healthy controls, of which Blautia, Ruminococcus2, Bilophila and Fusobacterium represented the major variances in PE microbiomes. Conversely,5 genera, including Faecalibacterium, Gemmiger, Akkermansia, Dialister and Methanobrevibacter, were significantly depleted in antepartum PE samples. Maternal blood pressure and liver enzyme levels were positively correlated to the PE-enriched genera such as Anaerococcus, Ruminococcus2, Oribacterium and Bilophila, while the fetal features (e.g. Apgar score and newborn birth weight) were positively correlated with PE-depleted genera and negatively correlated with PE-enriched genera. Moreover, maternal blood IL-6 level was positively associated with gut Bilophila and Oribacterium, whereas LPS level was negatively associated with Akkermansia. In terms of postpartum women, both the gut microbial composition and the PE-associated microbial alterations were highly consistent with those of the antepartum women. Conclusion: PE diagnosed in the third trimester of pregnancy is associated with a disrupted gut microbiota composition compared with uncomplicated pregnant women, which are associated with maternal clinical features (blood pressure level and liver dysfunction) and newborn birth weight. Moreover, these antepartum alterations in gut microbiota persisted 6 weeks postpartum.